Odpowiedź :
Q₁=Q₂ ciepło pobrane jest równe ciepłu oddanemu
m₁cΔt₁=m₂c(t₂-t₃)
Δt₁=40⁰C-10⁰C=30⁰C
t₃=40⁰C
m₁Δt₁=m₂(t₂-t₃)
m₁Δt₁/m₂=t₂-t₃
[m₁Δt₁/m₂]+t₃=t₂
t₂=[100kg×30⁰C:50kg]+40⁰C
t₂=100⁰C
m₁cΔt₁=m₂c(t₂-t₃)
Δt₁=40⁰C-10⁰C=30⁰C
t₃=40⁰C
m₁Δt₁=m₂(t₂-t₃)
m₁Δt₁/m₂=t₂-t₃
[m₁Δt₁/m₂]+t₃=t₂
t₂=[100kg×30⁰C:50kg]+40⁰C
t₂=100⁰C
Q₁=Q₂ ciepło pobrane jest równe ciepłu oddanemu
m₁cΔt₁=m₂c(t₂-t₃)
Δt₁=40⁰C-10⁰C=30⁰C
t₃=40⁰C
m₁Δt₁=m₂(t₂-t₃)
m₁Δt₁/m₂=t₂-t₃
[m₁Δt₁/m₂]+t₃=t₂
t₂=[100kg×30⁰C:50kg]+40⁰C
t₂=100⁰C
Mam nadzieję, że pomogłam ;]]
m₁cΔt₁=m₂c(t₂-t₃)
Δt₁=40⁰C-10⁰C=30⁰C
t₃=40⁰C
m₁Δt₁=m₂(t₂-t₃)
m₁Δt₁/m₂=t₂-t₃
[m₁Δt₁/m₂]+t₃=t₂
t₂=[100kg×30⁰C:50kg]+40⁰C
t₂=100⁰C
Mam nadzieję, że pomogłam ;]]